Only the dead within [large type] - Childs, Lisa (Childs, Lisa. Grave diggers, 2025)
"Between mysterious missing persons cases, unsolved murders, and the menacing specter of an eternally blood-thirsty grave digger's ghost, the town of Gold Creek, Michigan, has a grim reputation. Yet another teen has gone missing from the Gold Memorial Gardens, and Child Protective Services Investigator Claire Underwood isn't giving up until she finds him. For Claire, solving the case is more than business. Years ago, she lost a friend in that cemetery. Over time, the authorities deemed all the disappeared teens runaways, while local legend blamed the ghost of the murderous grave digger-much to the satisfaction of the Golds, also known as the "Ghouls." Claire has always suspected the Golds were involved, including in some recent murders among their own. Noah Gold is sick of being cast in the same light as his conniving, money-hungry family. He's a bit anti-social, but he's just as determined as Claire to unearth the truth-and finally bury the legend of the grave digger. With a common goal, he and Claire join forces, but it's a quest that puts them in mortal danger. Only with the help of the local sheriff-whose own brother vanished years ago-do they have a chance of surviving. Yet, the truth that awaits them is more terrifying than any ghost . . ."--